Optimal Standardized Ileal Digestible Arginine to Lysine Ratio for Japanese Quails in the Egg-Laying Phase - Tuesta, G. M. R.; Viana, G. S. [UNESP]; Barreto, S. L. T.; Muniz, J. C. L.; Reis, R. S.; Mencalha, I. R.; Hannas, M. (Facta-fundacio Arnco Ciencia Tecnologia Avicolas, 2018)
This study was conducted to determine the optimal standardized ileal digestible arginine to lysine (SID Arg:Lys) ratio for Japanese quails in the egg-laying phase. A total of two hundred forty-five 35-weekold Japanese quails (181 +/- 1.30 g initial body weight) were randomly assigned to five treatment groups with seven replicates of seven quails. Graded levels of L-Arginine were added to a basal diet in order to produce five SID Arg:Lys ratios (101, 106, 111, 116 and 121 %). Collected data were analyzed as one-way AN OVA and optimal ratio was estimated using polynomial regression model (linear and quadratic) based on performance traits. Statistical differences were considered for p<0.05. Graded SID Arg:Lys ratios did not affect performance traits assessed. Based on results, the SID Arg:Lys ratio of 101 % is sufficient to warrant proper performance of Japanese quails in the egg-laying phase.
Keywords: Coturnix coturnix japonica; digestible amino acids; ideal protein